Strategies to Cope with Teachers' Stress During and After the COVID-19 Pandemic: A South Africa Case Study - Thanduxolo Nomtshongwana; Andrea Mqondiso Buka; Nozuko Nqabeni (E-Journal of Humanities, Arts and Social Sciences, 2023)
This article focuses on how teachers are coping with stress in their schools during and after COVID-19. Teachers’ work by nature is stressful having to deal with various aspects such as ensuring that lesson notes are completed, students are performing as they should, and handling paperwork. This is combined with the lack of necessary resources to work efficiently. In their line of duty, teachers also face the dilemma of handling problematic behaviours of certain learners and there is a lot of work that must be done to protect teachers. The study adopted an interpretivism paradigm using the Social Cognitive Theory in which thematically analysed data was collected through interviews from 15 purposely selected participants from Chris Hani East Education in South Africa (CHEDE). The analysis of data revealed that learners are using drugs, which leads to a change in their behaviour at school, something that negatively affects the learning process and the teachers themselves. It also emerged from the data analysis that teachers have a lot of paperwork to deal with, with insufficient resources, teachers can use, especially during the time of COVID-19. This study found that teachers used WhatsApp groups, church services, and family support to cope with stress during COVID-19. The article recommends that the Department of Basic Education employs security measures to handle safety and protect students and teachers from the effect of illicit drug usage on the premises of schools which increases the stress levels of teachers. New programmes and policies must be formulated to equip students with enough knowledge about the danger of using drugs. The Department of Basic Education must also supply all schools with devices that can be used by teachers for online teaching and learning to facilitate learning.